Description of two new species of mole crickets from the genus Gryllotalpa (Orthoptera: Gryllotalpidae) in Cameroon, with a key to the Afrotropical parva group species - Simeu-Noutchom, Alain; Kekeunou, Sevilor; Wandji, Alain Christel; Nzike, Marcelle Mbadjoun; Nkwala, Alfiery Laurel Djomnang (Zootaxa, 2024)
A survey was conducted in two successive years, from March 2016 to March 2018, in three regions of Cameroon, during which two new species were collected in two regions and described. These two species, Gryllotalpa cameroonensis sp. nov. and Gryllotalpa tamessei sp. nov. were caught using the pitfall method in forests, agroforests, herbaceous fallows, and crop fields. From an ecological point of view, both new species were accidental in all vegetation types except crop fields, in which Gryllotalpa cameroonensis sp. nov. was accessory. Their habitat characteristics might require sandy soil for G. cameroonensis sp. nov. and silty soil for G. tamessei sp. nov., as well as low soil moisture and acid soil for both new species. The descriptions were followed by a revised key to the Afrotropical parva group species. This paper helps update the data on mole cricket biodiversity in Africa.